Aktivitas Antinosiseptif Fraksi Diklorometana Daun Kratom (Mitragyna speciosa Korth.) Rute Oral Pada Mencit Jantan Swiss - Luliana, Sri; Robiyanto, Robiyanto; Islamy, Muhamad Rido (Pharmaceutical Sciences and Research, 2018)
Kratom leaves (Mitragyna speciosa Korth.) is known to have an opioid-like analgesic effect. One of the main compound in kratom leaf is mitragynine which has strong affinity to opioid receptor. Kratom leaf has many pharmacological effects, one of them is as an antinoceptive agent. The purpose of this research to investigate the antinociceptive effect of dicholoromethane fraction from kratom leaf and determine the percentage of antinociceptive on male Swiss mice. The method used in this study was hot plate method. The animal subjects were divided to five groups: normal group CMC Na 0.5%, morphine 5.46 mg/kgBW, dicholoromethane fraction of kratom leaf doses 70, 140, and 280 mg/kgBW respectively. The subject response like jump, lick or lift up the back leg was considered as latent time parameter. The latent time was recorded at 0, 15, 30, 45, 60, 90, 105 and 120 minutes with cut-off time 15 seconds. Result data were analysed using One Way ANOVA and Post Hoc Test LSD. It showed the antinociceptive effect of discholoromethane fraction at dose 70, 140 and 280 mg/kgBW were significantly difference (p<0,05) with normal group. The conclusion of this study is the discholoromethane fraction of kratom leaf has antinociceptive activity. The percentage of antinocicetiptive from fraction group at dose 280 mg/kgBW(86%) was higher than the other two dose-groups (140 and 70 mg/kgBW) which were 81% and 51%.